Objek Wisata Situ Rawa Besar Kota Depok: Perubahan dan Tantangan di Masa Depan - Adhis Darussalam Pamungkas (Jurnal Ilmiah Wahana Pendidikan, 2021)
Depok City is actively revitalizing several situ starting in 2019 until the next few years. The potential to become a favorite tourist attraction is very large because the location is very strategic, located not far from Jalan Margonda Raya, close to Depok Baru Station and Public Transportation Terminal. The Depok City Government has carried out anointing, making jogging tracks and normalizing in the form of mud dredging in Situ Rawa Besar. Since the revitalization was completed, there has been one tourist boat and several micro-businesses, entertainment attractions in the jogging track area, this certainly adds to the tourist attraction. The problem that arises is that this tourist attraction does not yet have a Pokdarwis (tourism awareness group), based on the information of the Depok City Youth, Sports, Culture, and Tourism Office (Disporyata), the management should ideally be carried out by Pokdarwis because it is legally under the guidance and auspices of the Disporyata. The results of observations and interviews by researchers to key informants emphasized that the management of Situ Rawa Besar carried out by the local community has not been optimal. The conclusion of the study is the need for synergy between the government as a regulator and all elements of the local community in order to create a tourist attraction at Situ Rawa Besar that attracts many tourists, and of course benefits the local community in terms of economy.